Letter to the Editor: "Protective Bystander Effects Simulated with the State-Vector Model"-Hela X Skin Exposure to CS not Protective Bystander Response but Mammogram and Diagnostic X-Rays are - Bobby E. Leonard (SAGE Publishing, 2008)
The recent Dose Response journal article "Protective Bystander Effects Simulated with the State-Vector Model" ( Schollnberger and Eck1 2007 ) identified the suppressive (below natural occurring, zero primer dose, spontaneous level) dose response for HeLa x skin exposure to 137 Cs gamma rays ( Redpath et al 2001 ) as a protective Bystander Effect (BE) behavior. I had previously analyzed the Redpath et al (2001) data with a Microdose Model and conclusively showed that the suppressive response was from Adaptive Response (AR) radio-protection ( Leonard 2005 , 2007a ). The significance of my microdose analysis has been that low LET radiation induced single (i.e. only one) charged particle traversals through a cell can initiate a Poisson distributed activation of AR radio-protection. The purpose of this correspondence is to clarify the distinctions relative to the BE and the AR behaviors for the Redpath groups 137 Cs data, show conversely however that the Redpath group data for mammography ( Ko et al 2004 ) and diagnostic ( Redpath et al 2003 ) X-rays do conclusively reflect protective bystander behavior and also herein emphasize the need for radio-biologist to apply microdosimetry in planning and analyzing their experiments for BE and AR. Whether we are adamantly pro-LNT, adamantly anti-LNT or, like most of us, just simple scientists searching for the truth in radio-biology, it is important that we accurately identify our results, especially when related to the LNT hypothesis controversy.